(untitled) (Research, Society and Development, 2021)
Over the years, many dental programs have been implemented to care for babies in several municipalities in Brazil, but it is necessary to verify the effectiveness of these programs by evaluating the impact on oral health of children who have undergone this experience. Objective: To verify the presence of caries in mixed dentition in children aged 6 to 12 years, who had early care in the Dental Care Program for Babies (DCPB), when they were aged 0 - 3 years, comparing the results with a control group not exposed to preventive treatment, in the Oral Health service of the Family Health Strategy unit of São Bento, in the city of Santos. Method: Retrospective Cohort, where data were collected from 100 dental records of the children, 50 from each group. Descriptive statistical procedures and statistical analysis were performed using fisher’s test to measure the correlation between the variables. Results: In relation to deciduous teeth 26% of the children who participated in the DCPB presented caries lesions, while in the unexposed group 60% of the children presented caries lesions. In the evaluation of the presence of caries lesions in permanent teeth, there was almost no significant difference between the two groups, 10% in the group exposed to early treatment and 14% in the non-exposed group. Conclusion: A positive influence of Dental Care Program for Babies on oral health conditions was observed in children.